Learning Outcomes: How is the Experimentation of the AIR Learning Model? - Khadriah, Nopa Nur; Azizah, Nurul; Sa’idy, Sa’idy; Istihana, Istihana; Baharudin, Baharudin (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
This study examines how the experimentation of the Auditory, Intellectually, Repetition (AIR) learning model impacts students' learning outcomes in the Islamic Cultural History (SKI) subject at MTs Negeri 1 Bandar Lampung. The research is motivated by students' learning outcomes that have not met the Minimum Competency Criteria (KKM), which may be due to limitations in teaching methods and the influence of other external factors. This study employs a quantitative approach, with the population consisting of all eighth-grade students. The sample includes class VIII(A) as the experimental group and class VIII(B) as the control group. The data were analyzed using an independent t-test, yielding a final significance value of 0.070. This indicates that there is no statistically significant difference between the experimental and control groups. These results suggest that the AIR learning model does not produce significantly different learning outcomes compared to conventional teaching methods in this context. Therefore, further research is needed to optimize the application of the AIR learning model in the Islamic Cultural History (SKI) subject.